Friedman based analysis of perceived constraints among dairy farmers affected by national calamity in India - Lal, Sudhanand Prasad; Kadian, Kehar Singh; Kale, Rajiv Baliram; Shruti, Shruti (Indian Journal of Dairy Science, 2016)
The present study was conducted to study the perceived constraints faced by victims of the national calamity, i.e., Kosi flood that occurred in Bihar state of India way back on 18th August, 2008. Eight independent constraints were taken for the study based on secondary data and reconnaissance, which were later classified as 4 broad constraints. The study revealed that most severe constraint perceived by dairy farmers was ‘lack of knowledge regarding preparedness of natural calamity for livestock protection’. Asymptotic significance obtained from the Friedman test was 0.000 (p<0.01) with chi-square value of 84.457 with 3 degrees of freedom. Significance value showed, Monte Carlo Significance at 99 per cent confidence interval (CI) and hence, it could be interpreted that there was significant difference among the broad constraints faced by the dairy farmers. Friedman test identified that the most severe broad constraints perceived by dairy farmers was technical constraints followed by ‘economical constraints’, ‘physical constraints’, and ‘social constraints’. The study concluded that capacity building of the farmers regarding preparedness for the natural calamity is quintessential and in order to provide better and ensured remuneration of the milk and milk products village co-operatives should be established soon.